Neuroleptic malignant syndrome in clinical practices - Bugarinović Snežana M.; Đorđević Snežana S.; Savić Olivera R.; Mirjanić Tijana M. (Hospital Pharmacology, 2016)
Topic: Neuroleptic Malignant Syndrome is a rare but specific lethal reaction to neuroleptics / antipsychotics.It occurs in 0.02% to 3.3% of patients in the treatment applying conventional neuroleptic drugs. Neuroleptic malignant syndrome is associated with highly potent antipsychotic drugs. However, it can occur more frequently in patients treated with atypical antipsychotics such as clozapine. Topic position in medical public: Neuroleptic malignant syndrome is critical medical condition, potentially threatening complication associated with side effects of neuroleptic drugs. High levels of creatine kinase (CK) and leukocytosis are associated with neuroleptic malignant syndrome. Future action: Neuroleptic malignant syndrome as a psychiatric entity requires permanent research, early diagnosis, adequate therapy, exchange of clinical experiences, and what's of particular importance, rational antipsychotic administration.